2017
DOI: 10.3146/ps16-2.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interruption of Late Season Flowering to Improve Harvested Peanut Maturity

Abstract: Peanut (Arachis hypogaea) is a botanically indeterminate plant where flowering, fruit initiation, and pod maturity occurs over an extended time period during the growing season. As a result, the maturity and size of individual peanut pods vary considerably at harvest. Immature kernels that meet commercial edible size specifications negatively affect quality during processing due to their increased propensity for off flavors, higher moisture and water activity, and variable roasting properties. As peanuts progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Cultural practices that influence reproductive growth can affect the maturity profile and seed peanut quality. Lamb et al (2017) noted that timely applications of glyphosate and diflufenzopyr advanced the maturity profile of peanut via late-season flower abortion. Similarly, foliar fertilization may impact timeliness and viability of flowers, pegs, and pods, and may be expected to impact crop maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural practices that influence reproductive growth can affect the maturity profile and seed peanut quality. Lamb et al (2017) noted that timely applications of glyphosate and diflufenzopyr advanced the maturity profile of peanut via late-season flower abortion. Similarly, foliar fertilization may impact timeliness and viability of flowers, pegs, and pods, and may be expected to impact crop maturity.…”
Section: Introductionmentioning
confidence: 99%
“…For current experiments, late season flowers were hand removed; however, work over three years and multiple growing locations (small plot work) demonstrated that the input diflufenzopyr (BASF Biosciences) was effective at terminating late season flowers with corresponding approximate 400-500 lb/ acre yield increases with irrigation while also improving farmer stock grade (Lamb et al, 2017). Research is actively ongoing to evaluate this technology at commercial levels on yield and grade, in addition to its impact on post-harvest quality, including single seed oleic acid (%) distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Terminating flowers generated after about 90 days after planting, which have no potential to generate viable peanuts, has been shown to improve farmer stock yield and grade (Lamb et al, 2017). Late season flower termination also improves maturity distributions, and therefore may improve single kernel oleic acid (%) distributions.…”
mentioning
confidence: 99%
“…On the subject of optimizing maturity, work has been conducted on chemical control of late season flowering in order to influence the plant to behave more determinately by diverting resources away from late developing pods that will never reach harvestable weight in order to improve yield and/or grade of the already formed pods (Lamb et al 2017). While the specific chemicals/rates used in the study are not currently labelled for late-season use in peanut, there was proof of concept that chemical flower termination in peanut can increase yield and grade of peanut over the control.…”
mentioning
confidence: 99%